Discursive constructions of infant feeding: The dilemma of mothers' 'guilt'. (August 2013) - Williams, Kate; Kurz, Tim; Summers, Mark; Crabb, Shona
Recent feminist and sociological scholarship has problematised the underlying medical assumptions in the established literature on infant feeding by attending to the social and discursive construction of breastfeeding practice. Such work has suggested that the pervasive cultural discourse around breastfeeding as the 'morally correct' choice has implications for actual decisions and practices as well as subjective judgements and feelings, particularly those of guilt and inadequacy. The present study employs a discursive approach to analyse the ways in which childcare materials published since 2000 construct the issue of infant feeding. In particular, we focus upon the ways in which these materials attend to the possible implications of pro-breastfeeding discourses for mothers' subjective experience of guilt. We highlight a focus within the materials on not ' feeling ' guilty, as opposed to affirmations that formula feeding mothers are not guilty. The complex and potentially problematic nature of such public health messages in terms of gendered subjectivities is considered.